1995
DOI: 10.1055/s-2006-958041
|View full text |Cite
|
Sign up to set email alerts
|

Direct Enantiomeric Separation of Flavanones by High Performance Liquid Chromatography using Various Chiral Stationary Phases

Abstract: The performance of four chiral liquid chromatographic columns (Chiralcel OA, OJ, OC, OD) was studied with respect to the enantioseparation of flavanones and some derivatives. The effect of mobile phase composition on the retention time and stereo-selectivity was studied. A good enantioseparation (alpha up to 1.45) was achieved for most of the racemates. Further, the elution order of the enantiomers from the chiral stationary phases has been determined by using a circular dichroism based detection system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 6 publications
(6 reference statements)
0
20
0
Order By: Relevance
“…It is to be reported that Cyclobond I, a b-cyclodextrin stationary phase made up of cyclic glucoamyloses, was the most widely used column in the RP mode and in the normal phase mode to separate the 2R and 2S diastereomers of flavanone glycosides and benzoylated flavanone glycosides, respectively [130]. Work on the enantiomeric separation of flavanones and the diastereomeric separation of flavanone glycosides has also been reported by Ficarra et al who studied the performance of four chiral liquid chromatographic columns utilizing polysaccharide derivatives (i. e. Chiralcel OA, OJ, OC, OD) [131]. A good enantioseparation (a up to 1.45) was feasible for most of the racemates.…”
Section: Hplc Columnsmentioning
confidence: 98%
“…It is to be reported that Cyclobond I, a b-cyclodextrin stationary phase made up of cyclic glucoamyloses, was the most widely used column in the RP mode and in the normal phase mode to separate the 2R and 2S diastereomers of flavanone glycosides and benzoylated flavanone glycosides, respectively [130]. Work on the enantiomeric separation of flavanones and the diastereomeric separation of flavanone glycosides has also been reported by Ficarra et al who studied the performance of four chiral liquid chromatographic columns utilizing polysaccharide derivatives (i. e. Chiralcel OA, OJ, OC, OD) [131]. A good enantioseparation (a up to 1.45) was feasible for most of the racemates.…”
Section: Hplc Columnsmentioning
confidence: 98%
“…Furthermore, the enhancement of new insights on their chiral appearance in maturing process is of great interest due to their key position in the biosynthesis of polyphenolic compounds. Their chiral separation with the help of HPLC has been published in a few studies [7][8][9][10][11]. Up to now, the chiral separation of flavanones by CE has only been described by our working group [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, flavanone glycosides could also be resolved together with their aglycones and this was applied to analysis of naringenin enantiomers in tomato skin [67]. The performance of Chiralcel OA also indicated that 5-and 7-methoxyflavanone could be resolved as well as naringenin [65].…”
Section: Direct Methods Of Analysis: Chiral Stationary Phases (Csp)mentioning
confidence: 99%
“…Most of these investigations report the quantification of a variety of flavanones in citrus fruit juices and herbs [12,25,[59][60][61][62], or report the separation of flavanones on different stationary phases [63][64][65][66][67][68][69][70][71][72]. There is a paucity of investigations detailing the importance of stereospecific pharmacokinetics and pharmacodynamics of chiral flavanones.…”
Section: Introductionmentioning
confidence: 99%